Granulated Expanded Glass Manufacturing Method Using Electromagnetic Waves - Lucian Paunescu; Sorin Mircea Axinte; Felicia Cosmulescu; Marius Florin Dragoescu (Newinera Publisher, 2021)
The paper presents experimental results obtained in the process of experimental manufacture in a microwave oven of lightweight granulated glass aggregates. The process was conducted to obtain the highest dimensional class (between 18-23 mm), the almost spherical shape of the aggregates being facilitated by cold processing of raw spherical pellets (between 11-15 mm) containing the powder mixture formed by glass waste, borax. calcium carbonate, aqueous sodium silicate solution and water addition and then rotation of the high electromagnetic wave susceptible ceramic crucible containing raw pellets during the heat treatment at temperatures between 822-835 ºC. In terms of quality, the expanded glass aggregate granules are almost similar to those manufactured in conventional rotary kilns heated by burning fuel, having the following characteristics: bulk density of 0.17 g/cm3, compressive strength of 2.2 MPa, thermal conductivity of 0.047 W/m·K, water absorption of 1 vol. % and pore size between 0.3-0.6 mm. The experimental product has not yet been tested as a raw material in the manufacture of some light weight concretes, but the use of similar granulated glass aggregates manufactured in the world confirms the ability of this aggregate type to produce light weight and energy efficient concretes for building construction.